Incidence of the tradition-modernity relationship in the protection and conservation of the Historical Center of the city of Cuzco - Navarro Halanocca, René (2018)
This article refers to the problems presented by the protection and conservation of the cultural heritage of the historic centre of the city of Cusco, between the years of 1950-2005, subject of study factors are the tradition and modernity, to be nourished of ideological content, manipulated by the instances of power; political, economic, social and cultural. I tried to discover what are the levels of participation, influence that is found in the concept and practice of planning, urban planning, the new architecture and the discipline of conservation, in the effort to safeguard the local cultural heritage, however we find a confusing and contradictory scene, causing loss and destruction on the cultural heritage of the historic center of Cusco.